2013
DOI: 10.1007/s40520-013-0039-4
|View full text |Cite
|
Sign up to set email alerts
|

Ascertainment bias in dementias: a secondary to tertiary centre analysis in Central Italy and conceptual review

Abstract: The results of the study suggest that in a homogeneous area, AB is not interfering with diagnosis of AD or DLB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…The second caveat comes from the notion that our patient population was selected in a tertiary clinic including both a dementia and a movement disorder center, therefore burdened by an ascertainment bias toward dementia associated with parkinsonian features (i.e., DLB) ( Bonanni et al., 2013; Onofrj et al., 2010, 2013 ). Consequently, replication of our findings by other research groups are needed to validate quantitative EEG as a tool to predict the development of DLB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second caveat comes from the notion that our patient population was selected in a tertiary clinic including both a dementia and a movement disorder center, therefore burdened by an ascertainment bias toward dementia associated with parkinsonian features (i.e., DLB) ( Bonanni et al., 2013; Onofrj et al., 2010, 2013 ). Consequently, replication of our findings by other research groups are needed to validate quantitative EEG as a tool to predict the development of DLB.…”
Section: Discussionmentioning
confidence: 99%
“…Given that the principal aim of the study was to assess the predictive value of EEG in the early diagnosis of DLB, we enriched our study sample by the inclusion of MCI subjects who had at least 1 core or suggestive DLB symptom ( McKeith et al., 2005 ). Therefore, based on DLB prevalence in our dementia center ( Bonanni et al, 2013 ) we selected 3 MCI subjects with 1 core or suggestive DLB symptom, according to DLB diagnostic criteria ( McKeith et al, 2005 ) for every MCI subject without any DLB symptom.…”
Section: Methodsmentioning
confidence: 99%
“…The same meta-analysis found that DLB comprised 4.2% of community-based dementia populations. However, studies contributing to this meta-analysis observed prevalence rates ranging from 0 to 26% in individual cohorts [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Data on prospective cohorts of patients followed in our region independently of a history of PTSD showed that incidences of different dementia types were inside the variability ranges reported in prior epidemiological surveys and by other centers [ 49 ]. It is actually interesting to note that FTD incidence was 3.5% among patients with dementia, matching the percentage found in our retrospective cohort (5% on a population of 849 demented patients).…”
Section: Discussionmentioning
confidence: 99%
“…The retrospective part of the study is, undoubtedly,flawed by the typical biases of any retrospective study, including recall bias which might explain the lower incidence of PTSD among the dementia population (4%) as compared to incidence of dementia found in PTSD population evaluated in the prospective study (17%). Another possible limitation is that the prevalence of specific diagnoses is higher in a tertiary center as our University center, which is endowed with several advanced diagnostic tools ranging from SPECT, PET, MRI, fMRI 1.5–3 T, to laboratories of proteomics for assessment of CSF proteins, to genetic assessments of neurodegenerative disease to neuroimmunological essays, to complex neuropsychological evaluations [ 49 ].…”
Section: Discussionmentioning
confidence: 99%